Perceptions of Medical Students in Bandung towards Online and Offline Learning in the Anatomy Laboratory during the Covid-19 Pandemic - Mayasari, Wulan; Alsadila, Cindy Saskia; Veronica, Fifi (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Coronavirus Disease 2019 (COVID-19) that surged throughout the world in 2019 and engulfed Indonesia in 2020 had changed many aspects of people’s activities, significantly when altering the offline anatomy laboratories to online. This study aimed to determine the perspective of medical students in Bandung regarding the learning process in online and offline anatomy laboratories during the COVID-19 pandemic.Methods: This descriptive study had used modified questionnaires in previous research with a Likert scale. The respondents were 184 students from the 2018 or 2019 class of the Faculty of Medicine in Bandung, who participated in both online and offline anatomy laboratory learning methods. Sampling was carried out using the purposive sampling method. The data were presented in a frequency table and calculated by SPSS. Results: Regarding ‘material understanding’, most students (57.0%) disagreed that online anatomy laboratory activities were better than offline. In terms of ‘facilities and infrastructure’, 38.0% of students disagreed that online anatomy laboratory learning facilities were more adequate than offline. On the aspect of ‘teacher's perception’, most students agreed (39.0%) that teacher’s performance was better in online anatomy laboratory activities.Conclusion: This study shows that medical students prefer to combine online and offline anatomy laboratory activities.